Effects of water impact on optical properties of metallic mirror samples - Konovalov, V.G.; Solodovchenko, S.I.; Voitsenya, V.S.; Ryzhkov, I.V.; Shtan’, A.F.; Makhov, M.N. (Вопросы атомной науки и техники, 2019)
The effects of exposure in water or water steam on optical properties of mirror samples fabricated of different metals were studied. Materials of samples were: tungsten, beryllium, molybdenum, stainless steel, nickel, copper, rhodium, and amorphous alloys of two compositions. The material of the mirror was found to play a decisive role in degree of impact of water or water vapor on mirror degradation. The most strongly degraded Mo and Cu mirror samples, and the lowest degradation was observed for SS and Rh/SS mirror samples. The reflectance can be restored practically initial level when after water impact procedure the mirrors are exposed to ions of Ar plasma with energy ≥100 eV up to ion fluence >10¹⁹ ion/cm². Вивчено ефекти впливу води або водяної пари на оптичні властивості зразків дзеркал, виготовлених з різних металів: молібдену, вольфраму, нержавіючої сталі, нікелю, міді, родію, берилію і аморфних сплавів двох композицій. Було виявлено, що матеріал дзеркала відіграє вирішальну роль у мірі впливу води або водяної пари на деградацію дзеркала. Найбільш сильно деградували Mo- і Cu- зразки, а найнижча деградація спостерігалася для дзеркал SS і Rh/SS. Коефіцієнт віддзеркалення може бути відновлений до практично початкового рівня, якщо після впливу води дзеркала піддаються впливу іонів Ar-плазми з енергією ≥100 еВ до іонного флюєнса >10¹⁹ іонів/см². Изучены эффекты воздействия воды или водяного пара на оптические свойства образцов зеркал, изготовленных из разных металлов: молибдена, вольфрама, нержавеющей стали, никеля, меди, родия, бериллия и аморфных сплавов двух композиций. Было обнаружено, что материал зеркала играет решающую роль в степени воздействия воды или водяного пара на деградацию зеркала. Наиболее сильно деградировали Mo- и Cu- образцы, а самая низкая деградация наблюдалась для зеркал SS и Rh/SS. Коэффициент отражения может быть восстановлен до практически начального уровня, если после воздействия воды зеркала подвергаются воздействию ионов Ar-плазмы с энергией ≥100 эВ до ионного флюенса >10¹⁹ ионов/см².